Personalization in Customer Relationship Management : Balancing Data Privacy and Customer Experience - Muhammad Hanif Zahran; Muhammad Hibban Mikhail; Muharman Lubis (Acceleration, Quantum, Information Technology and Algorithm Journal, 2025)
Personalization through Customer Relationship Management (CRM) systems has become an essential way for organizations to improve customer experiences and strengthen loyalty. However, in order to create individualized interactions, a lot of customer data must be gathered and processed, which inevitably creates privacy concerns. This study seeks to explore how organizations can strike a healthy balance between personalization and data privacy, and how this balance shapes the overall customer experience. This study uses a literature review as its main method to better understand customer attitudes, desires, and concerns about data privacy and tailored services by consulting a variety of scientific sources and earlier research. This study aims to identify the key factors that shape customers’ perspectives on personalization and the protection of their personal data. The insights gained are intended to support organizations in designing CRM strategies that are effective and engaging, while also demonstrating a clear commitment to respecting customer privacy helping create a customer experience that feels more trusted, meaningful, and sustainable.